Keterbatasan dan Penguatan Sinergi Guru dan Orang Tua dalam Pendidikan Karakter Siswa - Amir, Amir; Lilianti, Lilianti; Adam, Adam (Journal of Leadership, Management and Policy in Education, 2025)
Character education is a fundamental component of the educational system aimed at fostering individuals with integrity, ethical awareness, and a strong sense of responsibility. This study examines the synergy between teachers and parents in shaping students’ character at SMA Negeri 1 Porehu, while also identifying existing challenges and effective strategies for improvement. Employing a qualitative case study approach, data were collected through in-depth interviews, participant observation, and document analysis involving nine key informants, including the school principal, teachers, and parents. The findings reveal that teacher–parent synergy remains limited due to ineffective communication and low parental participation in school activities. Nevertheless, initiatives such as the internalization of positive values through the “Morning Habituation” program and the establishment of regular communication forums between the school and parents have proven to enhance the effectiveness of character development. Supporting factors include well-structured school programs and active parental involvement, whereas major obstacles consist of value discrepancies between home and school environments and negative social influences. This study recommends strengthening collaborative-based character education programs by actively engaging parents in both instructional and character-building processes to ensure consistent and sustainable character formation among students.